Study of Pineapple Subgrade Substitution and Fermentation Time on The Physicochemical and Microbiological Characteristics of Cowpea Based (Vigna unguilata)-Based Probiotic Yoghurt - Ramadhanty, Chairunnisa Safira; Winarti, Sri; Pratiwi, Yunita Satya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Yoghurt is pasteurised animal milk, then fermented with lactic acid bacteria until the desired acidity, smell, and taste are achieved. The main ingredients for making yoghurt in this study are cowpea and pineapple. Cowpea (Vigna unguiculata L.) is a high-protein local food, ranking after soybeans. Subgrade pineapple is a smaller pineapple fruit with a length ? 9.9 cm and a weight ? 0.4 kg, which is rich in antioxidants and has a high vitamin C content. The purpose of this study was to analyse the effect of subgrade pineapple substitution and fermentation time on the physicochemical and microbiological characteristics of cowpea probiotic yoghurt, and then determine the best treatment combination of these variations. The method used was a Completely Randomised Design (CRD) factorial pattern, with Factor I being subgrade pineapple juice substitution (10%, 20%, and 30%) and Factor II being fermentation time (15 hours, 20 hours, and 25 hours). The data obtained were analysed using ANOVA followed by DMRT, further tests at the 5% level. The results showed a significant interaction (p ? 0.05). Yoghurt with 30% subgrade pineapple substitution and 20 hours fermentation time treatment is the best treatment that produces yogurt with a total acid value of 1.10%, pH value of 3.53, viscosity of 462.2 mPa.s., vitamin C 37.75 mg/100ml, total LAB 8.44 log CFU/ml, antioxidant 33.90 mg AEAC/g, protein 0.70%. Contribution to Sustainable Development Goals (SDGs)SDG 2 – Zero HungerSDG 3 – Good Health and Well-beingSDG 12 – Responsible Consumption and ProductionSDG 9 – Industry, Innovation, and Infrastructure